The microenvironment in the development of MASLD-MASH-HCC and associated therapeutic in MASH-HCC - Wu, Qiulin; Yang, Yan; Lin, Shixun; Geller, David A.; Yan, Yihe (Frontiers in Immunology, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a series of obesity-related metabolic liver diseases, ranging from relatively benign hepatic steatosis to metabolic-associated steatohepatitis (MASH). With the changes in lifestyle, its incidence and prevalence have risen to epidemic proportions globally. In recent years, an increasing amount of evidence has indicated that the hepatic microenvironment is involved in the pathophysiological processes of MASH-induced liver fibrosis and the formation of hepatocellular carcinoma (HCC). The hepatic microenvironment is composed of various parenchymal and non-parenchymal cells, which communicate with each other through various factors. In this review, we focus on the changes in hepatocytes, cholangiocytes, liver sinusoidal endothelial cells (LSECs), hepatic stellate cells (HSCs), Kupffer cells (KC), dendritic cells (DC), neutrophils, monocytes, T and B lymphocytes, natural killer cells (NK), natural killer T cells (NKT), mucosal-associated invariant T cells (MAIT), γδT cells, and gut microbiota during the progression of MASLD. Furthermore, we discuss promising therapeutic strategies targeting the microenvironment of MASLD-MASH-HCC.